Outdoor Laboratories in Social Studies Learning: A Systematic Review and Pedagogical Implications: Laboratorium Luar Ruang dalam Pembelajaran Ilmu Sosial: Tinjuan Sistematis dan Implikasi Pedagogis - gunawan; Fredy Hermanto; Amrin Ma’ruf; Latif Hendro Wibowo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Social science faces the challenge of bridging the gap between theoretical concepts and the dynamics of social reality. Conventional learning models tend to limit learning experiences, making it difficult to understand the complexity of an ever-changing social reality. This study aims to identify forms of outdoor laboratories and learning models that can support the learning process in the social sciences. The research method employed a literature review, with literature searches conducted through Publish or Perish, Consensus, Google Scholar, Gate, and Scopus using the keywords: "outdoor laboratory, outdoor activity, social science laboratory, living laboratory, and outdoor learning. Data analysis used thematic analysis to identify key patterns in the concepts, implementation, and impacts of outdoor laboratory-based learning. The results indicate that outdoor laboratories have been understood as spaces for knowledge production grounded in direct interaction with communities. Suitable learning models include outdoor learning with a design thinking approach and the Living Lab model, which emphasizes social innovation. The use of outdoor laboratories has a positive impact on cognitive aspects by enhancing critical thinking, analytical skills, and problem-solving abilities, as well as on social-emotional aspects by strengthening leadership character and awareness of environmental and local cultural issues. However, its implementation faces challenges related to human resources, infrastructure limitations, and integration with the formal curriculum. This research contributes to the development of a conceptual framework for outdoor laboratories to facilitate more contextual, authentic, and meaningful social science learning.